Foliar Symptoms Triggered by Ozone Stress in Irrigated Holm Oaks from the City of Madrid, Spain - Calderon Guerrero, Carlos; Guenthardt-Goerg, Madeleine S.; Vollenweider, Pierre (PLOS ONE, 2013)
Background: Despite abatement programs of precursors implemented in many industrialized countries, ozone remains the principal air pollutant throughout the northern hemisphere with background concentrations increasing as a consequence of economic development in former or still emerging countries and present climate change. Some of the highest ozone concentrations are measured in regions with a Mediterranean climate but the effect on the natural vegetation is alleviated by low stomatal uptake and frequent leaf xeromorphy in response to summer drought episodes characteristic of this climate. However, there is a lack of understanding of the respective role of the foliage physiology and leaf xeromorphy on the mechanistic effects of ozone in Mediterranean species. Particularly, evidence about morphological and structural changes in evergreens in response to ozone stress is missing. Results: Our study was started after observing ozone -like injury in foliage of holm oak during the assessment of air pollution mitigation by urban trees throughout the Madrid conurbation. Our objectives were to confirm the diagnosis, investigate the extent of symptoms and analyze the ecological factors contributing to ozone injury, particularly, the site water supply. Symptoms consisted of adaxial and intercostal stippling increasing with leaf age. Underlying stippling, cells in the upper mesophyll showed HR-like reactions typical of ozone stress. The surrounding cells showed further oxidative stress markers. These morphological and micromorphological markers of ozone stress were similar to those recorded in deciduous broadleaved species. However, stippling became obvious already at an AOT40 of 21 ppm.h and was primarily found at irrigated sites. Subsequent analyses showed that irrigated trees had their stomatal conductance increased and leaf life -span reduced whereas the leaf xeromorphy remained unchanged. These findings suggest a central role of water availability versus leaf xeromorphy for ozone symptom expression by cell injury in holm oak.
APSAPSThe following values have no corresponding Zotero field: pub-location: 1160 BATTERY STREET, STE 100, SAN FRANCISCO, CA 94111 USA publisher: PUBLIC LIBRARY SCIENCE
Keywords: Holm oak; Mediterranean climate; natural vegetation; Ozone; Stomatal uptake

Nitrogen dioxide (NO2) uptake by vegetation controlled by atmospheric concentrations and plant stomatal aperture - Chaparro-Suarez, I. G.; Meixner, F. X.; Kesselmeier, J. (Atmospheric Environment, 2011)
Nitrogen dioxide (NO2) exchange between the atmosphere and ﬁve European tree species was investigated in the laboratory using a dynamic branch enclosure system (consisting of two cuvettes) and a highly speciﬁc NO2 analyzer. NO2 measurements were performed with a sensitive gas phase chemiluminescence NO detector combined with a NO2 speciﬁc (photolytic) converter, both from Eco-Physics (Switzerland). This highly speciﬁc detection system excluded bias from other nitrogen compounds. Investigations were performed at two light intensities (Photosynthetic Active Radiation, PAR, 450 and 900 mmol m2 s 1 ) and NO2 concentrations between 0 and 5 ppb. Ambient parameters (air temperature and relative humidity) were held constant. The data showed dominant NO2 uptake by the respective tree species under all conditions. The results did not conﬁrm the existence of a compensation point within a 95% conﬁdence level, though we cannot completely exclude emission of NO2 under very low atmospheric concentrations. Induced stomatal stricture, or total closure, by changing light conditions, as well as by application of the plant hormone ABA (Abscisic Acid) caused a corresponding decrease of NO2 uptake. No loss of NO2 to plant surfaces was observed under stomatal closure and species dependent differences in uptake rates could be clearly related to stomatal behavior
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Deposition; Gas exchange; Nitrogen dioxide; Stomatal uptake; Vegetation

Ozone uptake by an evergreen Mediterranean Forest () in Italy. Part I: Micrometeorological flux measurements and flux partitioning - Gerosa, G.; Vitale, M.; Finco, A.; Manes, F.; Denti, A.; Cieslik, S. (Atmospheric Environment, 2005)
Ozone, water and energy ﬂuxes have been measured over a Mediterranean evergreen forest in Central Italy from August to October 2003 with the eddy-correlation technique in order to evaluate the amount of ozone taken up by plants in dry summer and in mild autumn conditions. The stomatal ozone ﬂuxes have been calculated using the analogy with water vapor ﬂuxes inside the stomata, which are easily measurable. The total ozone dose was obtained by integrating the stomatal ﬂuxes over time. Stomatal ﬂux resulted a minor part (31.5%) of the total ozone ﬂux over the forest ecosystem. The main part of ozone deposition follows non-stomatal pathways. Chemical sink seems to play a relevant role in the morning non-stomatal deposition. Stomatal uptake is enhanced by water availability but, on the average, it does not exceed the 34.4% of the total ozone ﬂux. A comparison between the cumulated stomatal ozone ﬂuxes and the currently used AOT40 exposure index highlighted important distortions introduced by this index. AOT40, which do not take into account plant physiology, lead to substantial overestimation of ozone risk, particularly when water supply is limited, as occurs frequently in Southern European and Mediterranean areas.
Keywords: Holm oak; mediterranean forest ecosystem; ozone deposition; Stomatal uptake

Ozone uptake by an evergreen Mediterranean Forest () in Italy. Part I: Micrometeorological flux measurements and flux partitioning - Gerosa, G; Vitale, M; Finco, A; Manes, F; Denti, A; Cieslik, S (Atmospheric Environment, 2005)
Ozone, water and energy ﬂuxes have been measured over a Mediterranean evergreen forest in Central Italy from August to October 2003 with the eddy-correlation technique in order to evaluate the amount of ozone taken up by plants in dry summer and in mild autumn conditions. The stomatal ozone ﬂuxes have been calculated using the analogy with water vapor ﬂuxes inside the stomata, which are easily measurable. The total ozone dose was obtained by integrating the stomatal ﬂuxes over time. Stomatal ﬂux resulted a minor part (31.5%) of the total ozone ﬂux over the forest ecosystem. The main part of ozone deposition follows non-stomatal pathways. Chemical sink seems to play a relevant role in the morning non-stomatal deposition. Stomatal uptake is enhanced by water availability but, on the average, it does not exceed the 34.4% of the total ozone ﬂux. A comparison between the cumulated stomatal ozone ﬂuxes and the currently used AOT40 exposure index highlighted important distortions introduced by this index. AOT40, which do not take into account plant physiology, lead to substantial overestimation of ozone risk, particularly when water supply is limited, as occurs frequently in Southern European and Mediterranean areas.
Keywords: Holm oak; mediterranean forest ecosystem; ozone deposition; Stomatal uptake